Cisadane Festival Local Tradition as a Learning Resources in Improving Students’ Writing Skill on Descriptive Text - Nuraini, Hery; Muhyidin, Asep; Jamaludin, Ujang; Leksono, Suroso Mukti (Universitas Alma Ata, 2024)
Understanding descriptive text in learning English is not easy for Al-Husna Senior High School at tenth grade. Most of students still found difficulties in elaborating the text such as find the idea, explore the sub-topic, and separate the characteristics of descriptive text. The aim of this study was to investigate the used of local culture as a learning resource in improving students’ writing skill on descriptive text. This study applied descriptive qualitative with the total subjects of research were 35 students. Written test and interview were used in collecting the data. The result of written test showed that the students’ average score on the post-test had increased compared to the average score on the pre-test. The result of written test was in line with the result of interview which showed a positive response to the use of local culture in learning descriptive texts. All respondents felt happy and interested in learning descriptive text based on local culture of Tangerang City, so they could get to know this culture more closely. Using cultural festivals as a learning resource not only improve their writing skill on descriptive text but also helps students develop an appreciation for local culture, increases their awareness of the region’s rich cultural heritage, and develops a sense of pride in their cultural identity. These findings demonstrate the importance of integrating more local cultural festivals into the learning curriculum to enrich students’ writing skills through strengthening connections with local culture and traditions.Keywords: Cisadane festival, Descriptive text, Learning resources, Writing skill.